Effectiveness of Using Video Tutorials in Hair and Bun Styling Courses in the Department of Makeup and Beauty, FPP UNP - Itriano, M. Hafanza; Zuwirna, Zuwirna; Eldarni, Eldarni; Amsal, Mutiara Felicita (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Learning is a very important part of the educational process and needs attention. One lesson that can be used to simplify the educational process or teaching and learning activities is through audio-visual media. Audio visual media is media that combines audio and visuals by stimulating hearing and sight in the process of conveying messages or information. One of the audio-visual learning media is video tutorial media. This research aims to determine the effectiveness of implementing video tutorial media in the Hair and Bun Styling course at the Department of Makeup and Beauty, FPP UNP. The results obtained in this research are the results of a hypothesis using the Test formulaℎit was found that tcount = 2.202 was greater than ttable = 2.021. From the explanation above, it can be concluded that there is effectiveness of Video Tutorial Media in the Hair and Bun Styling course in the Department of Makeup and Beauty, FPP UNP